The Influence of Brand Personality, Brand Love, and Brand Image on Brand Advocacy (A Study of iPhone Users in Cirebon) - Triyana Aldi Saprudin; Ramlah Puji Astuti; Soesanty Maulany (Interdisciplinary Social Studies, 2026)
This study aims to analyse the influence of brand personality, brand love, and brand image on brand advocacy among iPhone users in Cirebon City. Amid fierce competition in the premium smartphone market, the iPhone has managed to maintain high user loyalty despite not holding the largest overall market share. Using a quantitative approach with a cross-sectional design, data were collected from 259 respondents through purposive sampling and analysed using SmartPLS 4.0. The results of the study show that brand personality, brand love, and brand image simultaneously have a significant effect on brand advocacy, with a combined contribution of 74.3%. Partially, brand love proved to be the most dominant predictor, indicating that deep emotional attachment is more effective in driving voluntary advocacy behaviour than rational factors alone. Brand personality and brand image also contribute positively by strengthening users' self-expression and sense of social prestige. The implications of this study suggest that Apple's marketing strategy should continue to focus on strengthening emotional branding and maintaining its premium reputation. The primary limitation of this study lies in its geographical focus on a single local area; future studies are therefore recommended to expand demographic and geographic coverage for broader generalisability